2009
DOI: 10.3168/jds.2009-2261
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between globular proteins and procyanidins of different degrees of polymerization

Abstract: Interactions of proteins with phenolic compounds occur in food products containing vegetable sources, such as cocoa, cereals, or yogurts containing fruit. Such interactions can modify protein digestion and protein industrial properties. Noncovalent interactions between globular proteins (proteins important in industry) and procyanidins (phenolic compounds present in large quantity in fruits) were studied. The affinity constants between procyanidins of various average degrees of polymerization (DP) and lysozyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 36 publications
3
56
0
Order By: Relevance
“…39 A previous study on globular protein−procyanidins interactions showed that the higher the degree of polymerization, the higher the affinity constant. 8 Poncet-Legrand et al 40 showed that low polymerized procyanidins are more susceptible to selfassociation than higher polymerized procyanidins and this self-association tendency could limit the association with other compounds such as pectins. Frazier et al 16 showed that grape seed proanthocyanidins in the presence of BSA revealed very weak interactions and suggested that a lack of flexibility in the proanthocyanidins may have contributed to their low affinity.…”
Section: ■ Discussionmentioning
confidence: 99%
“…39 A previous study on globular protein−procyanidins interactions showed that the higher the degree of polymerization, the higher the affinity constant. 8 Poncet-Legrand et al 40 showed that low polymerized procyanidins are more susceptible to selfassociation than higher polymerized procyanidins and this self-association tendency could limit the association with other compounds such as pectins. Frazier et al 16 showed that grape seed proanthocyanidins in the presence of BSA revealed very weak interactions and suggested that a lack of flexibility in the proanthocyanidins may have contributed to their low affinity.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Phenolics such as caffeic, chlorogenic and ferulic acids bind to globular proteins (Li et al, 2010) and readily form insoluble complexes with major peanut allergens, especially Ara h 1 and Ara h 2, and such complexation reduces immunoglobulin E binding (Chung & Champagne, 2009). A recent study provided data on increasing binding affinities of oligomerized polyphenols to globular proteins with increasing degree of polymerization (Prigent et al, 2009). Similarly, a positive correlation was found between the degree of polyphenol oligomerization and inhibition of elastase (Bras et al, 2010) due to an increased number of protein interacting groups.…”
Section: Discussionmentioning
confidence: 99%
“…Tannins were shown to reduce saliva-lubricating ability, both by increasing friction and by reducing its viscosity (Prigent et al, 2009;Prinz & Lucas, 2000). Some authors have shown that the interaction between tannin and salivary proteins is indeed involved in the mechanism of astringency (Horne, Hayes, & Lawless, 2002;Kallithraka, Bakker, & Clifford, 1998).…”
Section: Introductionmentioning
confidence: 99%